PENGARUH UPAH MINIMUM REGIONAL DAN JUMLAH PENDUDUK TERHADAP PENERIMAAN PAJAK BUMI DAN BANGUNAN DI DESA SLATRI, KECAMATAN LARANGAN, KABUPATEN BREBES - Mutholib, Abdul; Dumadi, Dumadi; Zaman, M. Badrun (LP2M Universitas Bina Bangsa, 2025)
Land and building tax (PBB) revenue will increase if the regional minimum wage (UMR) is raised. The higher and the increasing population can also add to the increase in PBB revenue in Slatri village. This study aims to determine the influence of UMR and population on UN revenue. Primary data was used in this quantitative research in the form of questionnaire distribution. The research population is all land and building taxpayers in Slatri village as many as 11,203 taxpayers with convenience sampling techniques, obtained by 100 respondents with an error rate of 10%. The analysis technique used is in the form of a multiple linear regression model with the help of IBM SPSS. The results of the study can be concluded that UMR has a significant positive effect on UN revenue and the number of population also has a significant positive effect on UN revenue. Simultaneously, UMR and population have a significant positive effect on UN revenue